PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) DI KELAS IV SDN 33 PASAMAN - Astati Muheni; Farida S (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Abstrak This research is based on the results of field research, namely the low learning outcomes of students due to the lack of learning activities involving students because the learning process is still centered on the teacher, so that students are still less active in the learning process. This study aims to describe how to improve student learning outcomes in IPAS learning using the Problem Based Learning (PBL) model in class IV SDN 33 Pasaman. This type of research is classroom action research (CAR) using qualitative and quantitative approaches. This research was conducted in two cycles, with research procedures consisting of planning, implementation, observation and reflection. The research data obtained are related to the learning outcomes of the Problem Based Learning (PBL) model. Data collection techniques are in the form of tests and non-tests. The subjects of this study were class teachers as observers, researchers as practitioners or teachers, and 18 students of grade IV SDN 33 Pasaman. The results of the study showed that: first, the teaching module of cycle I obtained an average of 85.4% (B), increasing in cycle II to 95.8 (SB). Second, the results of the implementation of learning aspects of teachers in cycle I obtained an average of 82.14 (B), increasing in cycle II to 96.42% (SB). Third, the results of the implementation of learning aspects of students in cycle I obtained an average of 82.14% (B), increasing in cycle II to 96.42% (SB). Fourth, the learning outcomes of students in cycle I obtained an average of 74.41 (C), increasing in cycle II to 81.39 (B). Thus, it can be concluded that the Problem Based Learning (PBL) model can improve student learning outcomes in IPAS learning in Class IV SDN 33 Pasaman.